PENGEMBANGAN MEDIA PEMBELAJARAN KARTU KATA BERGAMBAR (FLASH CARD) UNTUK MELATIH KEMAMPUAN MEMBACA PEMULA DI SD NEGERI 2 BAGIK PAYUNG - Faizatul Rodiah, Baiq (Papanda Publisher, 2023)
This research aims to develop a learning media in the form of flashcards for training beginner reading skills in SD Negeri 2 Bagik Payung and aims to determine the feasibility of the flashcard media, as well as to understand how students respond to the flashcard media. This research uses the ADDIE development model developed by Robert Maribe Branch, which consists of five steps: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. This research was conducted with 15 first-grade students at SD Negeri 2 Bagik Payung. Data for this research and development were obtained from expert validation of media, expert validation of content, and student response questionnaires. Data collection techniques included interviews, observations, and student response questionnaires. The research and development instruments used validation sheets and student response questionnaires. This research resulted in a product in the form of flashcards as a learning media based on assessments from media experts and content experts. The media validation results fell into the